2017
DOI: 10.18761/perspectivas.v3i2.227
|View full text |Cite
|
Sign up to set email alerts
|

Uma Revisão dos Artigos Publicados no Journal of Applied Behavior Analysis (JABA) sobre Comportamento Verbal e Autismo entre 2008 e 2012

Abstract: O presente estudo faz uma breve apresentação sobre o transtorno do espectro autista (TEA), bem como sobre as categorias gerais de trabalho referentes ao ensino de linguagem para alunos da educação especial na análise aplicada do comportamento. O objetivo foi realizar uma revisão dos artigos publicados no Journal of Applied Behavior Analysis (JABA) entre 2008 e 2012. A revisão foi realizada por meio da base de dados PubMed e o critério de seleção dos artigos incluiu as palavras comportamento verbal e autismo no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
0
8
0
6
Order By: Relevance
“…Compared to other review studies, it is observed that when the inclusion criteria of the papers are more refined, the number of papers identified in echoic teaching drastically reduces. While Kubina, Wolf and Kostewicz (2009), Martone and Santos-Carvalho (2012) and Sautter and Le Blanc (2006), found a sample of studies that aimed to teach echoic from 9 to 11% of the sample, this study and Souza, Akers and Fisher (2017) found respectively 1.25% of the sample and 2.3%.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Compared to other review studies, it is observed that when the inclusion criteria of the papers are more refined, the number of papers identified in echoic teaching drastically reduces. While Kubina, Wolf and Kostewicz (2009), Martone and Santos-Carvalho (2012) and Sautter and Le Blanc (2006), found a sample of studies that aimed to teach echoic from 9 to 11% of the sample, this study and Souza, Akers and Fisher (2017) found respectively 1.25% of the sample and 2.3%.…”
Section: Discussionmentioning
confidence: 54%
“…However, among papers found by Kubina, Wolf and Kostewicz (2009), not all studies were included because participants had no diagnosis of ASD (Lowe, Horne, Harris, & Randle, 2002;Stewart, Barnes-Holmes, Roche, & Smeets, 2001;Yoon & Bennett, 2000). Regarding the study conducted by Martone and Santos-Carvalho (2012), the authors do not present the references of studies that aimed to teach echoic, and it is not possible to identify similarities or differences in the search results. Regarding the study conducted by Souza, Akers and Fisher (2017), two studies were removed from the sample because not all participants had a diagnosis of ASD (Tarbox, Madrid, Aguilar, Jacobo, & Schiff 2009) and because it did not appear in the survey conducted with the specific descriptors and selected databases (Speckman-Collins, Lee Park, .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations